Arctic sea ice motion change and response to atmospheric forcing between 1979 and 2019. (3rd September 2021) - Zhang, Fanyi; Pang, Xiaoping; Lei, Ruibo; Zhai, Mengxi; Zhao, Xi; Cai, Qiongqiong
Abstract: Quantification of the spatial variability and long‐term changes of Arctic sea ice motion is important for understanding the mechanisms of rapid Arctic sea ice decline because sea ice motion determines ice mass advection, outflow, thickness redistribution, as well as the formation of leads and ridges associated with ice deformation. The spatiotemporal changes in Arctic sea ice motion between 1979 and 2019 and their responses to atmospheric forcing were analysed using satellite‐derived sea ice motion products and atmospheric reanalysis data. The pan‐Arctic average sea ice drift speed increased significantly for all seasons between 1979 and 2019 ( p < .001). Rates of increase were higher in autumn and winter than in spring and summer. Spatially, rates of increase in the peripheral seas in the Pacific sector—the Beaufort, Chukchi and East Siberian Seas—were higher than in the central Arctic Ocean and the peripheral seas in the Atlantic sector—the Kara and Laptev Seas. On the contrary, Arctic wind speed increased significantly only in autumn ( p < .01). However, the correlation between wind speed and ice speed was the lowest in this season, suggesting that wind forcing is unable to completely account for drift speed increase. In general, the trends in above‐average drift speeds—retrieved from grid cells with the relatively high drift speeds—were statistically significant and were larger than that in average drift speeds probably because of enhanced response of ice motion to extreme wind forcing. The influence of the Arctic Oscillation, Beaufort High, and North Atlantic Oscillation on the zonal ice speed was symmetrical between the Pacific and Atlantic sectors of the Arctic Ocean, while the influence of the Dipole Anomaly and the east–west surface air pressure gradient in central Arctic on the meridional ice speed was distributed in an annular pattern and was the strongest along the Transpolar Drift Stream. Abstract : Arctic sea ice drift speed increased significantly between 1979 and 2019, with distinct seasonal and spatial variabilities. The increase rate is more pronounced in extremely high drift speed than that in average drift speed. Changes in zonal and meridional ice speeds were significantly related to different atmospheric circulation patterns.